Overlap phenotypes of the left ventricular noncompaction and hypertrophic cardiomyopathy with complex arrhythmias and heart failure induced by the novel truncated DSC2 mutation - Lin, Yubi (BioMed Central Ltd, 2022)
10.1186/s13023-021-02112-9